Microbial community and short-chain fatty acid profile in gastrointestinal tract of goose. (15th March 2018) - Yang, H; Xiao, Y; Gui, G; Li, J; Wang, J; Li, D
Abstract: Goose is an economically important herbivore waterfowl supplying nutritious meat and eggs, high-quality liver fat, and feathers. However, biogeograhpy of the gut microbiome of goose remains limited. The aim of this study was to investigate the microbiota inhabiting 7 different gastrointestinal locations (proventriculus, gizzard, duodenum, jejunum, ileum, cecum, and rectum) of 180-day-old geese and the short-chain fatty acids (SCFA) of their metabolites based on 16S rRNA gene sequences and gas chromatography, respectively. Consequently, 3, 886, 340 sequences were identified into 29 phyla and 359 genera. Proteobacteria, Firmicutes, Bacteroidetes, Cyanobacteria, and Actinobacteria were the major phyla, in which Bacteroidetes (28%) and Fusobacteria (0.8%) in the cecum were significantly higher than those in other sections (∼4.4 and 0.1%, respectively). In addition, Cyanobacteria in the gizzard (4.9%) was significantly higher than those in other gut sections except the proventriculus (2.4%). At the genus level, Bacteroides was the most dominant group in the cecum at 23.7%, which was much more than those in the 6 other sections (less than 4.6%). Moreover, Faecalibacterium and Butyricicoccus were significantly high in the cecum ( P < 0.05). Results of SCFA showed that acetic and butyric acids in the cecum were significantly higher than those in the 6 other sections ( P < 0.05); this result was consistent with the high abundance of Bacteroides, Faecalibacterium, Prevotella, and Butyricicoccus in the cecum. Additionally, isobutyric, isovaleric, and valeric acids were found only in the cecum. The different microbial compositions among the 7 gastrointestinal locations might be a cause and consequence of gut functional differences. All these results could offer some information for future study of the relationship between gastrointestinal microbiota and the ability of fiber utilization and adaptability.